Method for regulating and controlling cooling time after Joule heating and high-entropy oxide electrocatalyst based on method

By adjusting the mass-area ratio of the graphite substrate, and using Joule heating equipment to regulate the cooling time, an efficient high-entropy oxide electrocatalyst was prepared, which solved the problem of poor catalytic performance of OER in the prior art and achieved significant improvement in catalytic performance.

CN119592990AActive Publication Date: 2025-03-11WUHAN UNIV

Patent Information

Application Number
CN202411663675.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-11
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the prior art, Joule heating equipment cannot regulate the cooling time, resulting in poor OER catalytic performance of high entropy oxide electrocatalysts.

Method used

By adjusting the mass-area ratio of the graphite substrate, using Joule heating equipment to achieve precise regulation of the cooling time in the range of 1100 K to 2200 K, a high entropy oxide electrocatalyst with large specific surface area and stable phase structure was prepared.

Benefits of technology

The transient cooling of high-entropy oxide electrocatalysts was achieved, which significantly improved the OER catalytic performance. The overpotential of the electrocatalyst with a cooling time of 0.3 s was only 219 mV at a current density of 10 mA cm-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592990A_ABST
    Figure CN119592990A_ABST
Patent Text Reader

Abstract

The invention provides a method for regulating and controlling cooling time after Joule heating and a high-entropy oxide electrocatalyst based on the method, and belongs to the technical field of electrocatalytic electrolysis of water. According to the method, the relationship between the graphite substrates with different mass area ratios and the cooling time is determined based on the Newton's law of cooling by carrying out volume segmentation on the graphite substrates; the structure and performance of the high-entropy oxide electrocatalyst are regulated and controlled on the basis of a cooling time regulation and control strategy; the prepared high-entropy oxide electrocatalyst has excellent oxygen evolution reaction catalytic activity in an alkaline environment, the structure of the high-entropy oxide electrocatalyst with the cooling time of 0.3 s is a nanowire assembled by fine nano-particles, the high-entropy oxide electrocatalyst shows the optimal electrochemical performance, and under the current density of 10 mA cm <-2 >, the high-entropy oxide electrocatalyst has excellent oxygen evolution reaction catalytic activity. And the overpotential is only 219 mV. The method provided by the invention is simple and efficient, and can be widely applied to preparation and performance optimization of the electrocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic water electrolysis, and in particular to a method for regulating cooling time after Joule heating and a high entropy oxide electrocatalyst based thereon. Background Art

[0002] Producing hydrogen through water electrolysis has become an effective strategy to address the fossil fuel energy crisis. However, during water electrolysis, the anodic oxygen evolution reaction (OER) involves complex four-electron transfer and has a slow kinetics, resulting in significant energy loss and limiting the overall energy efficiency. Although noble metal catalysts such as RuO 2 and IrO 2 Although it exhibits excellent OER catalytic performance, its large-scale use in practical applications is limited due to resource scarcity. Therefore, the development of OER catalysts with high activity, durability and low cost has become the focus of current research.

[0003] In recent years, high-entropy materials have shown unique diversified compositions and adjustable electronic structures, which make them show advantages in catalysis and mechanical properties that are difficult to match with traditional materials. Currently, researchers have developed a variety of methods for synthesizing high-entropy materials, including melting, ball milling, and magnetron sputtering. However, these traditional methods are usually time-consuming and energy-intensive, and have obvious limitations in large-scale production. In order to overcome these challenges, it is urgent to explore low-cost, low-energy consumption, and rapid synthesis methods.

[0004] Joule heating is an emerging electrothermal conversion technology that can rapidly heat samples to thousands of degrees Celsius within milliseconds. Compared with other rapid heating strategies, such as plasma flame method and microwave heating method, Joule heating can not only significantly shorten the reaction time and reduce energy consumption, but also maintain the single-phase structure and uniformity of the material by controlling the heating time. Therefore, Joule heating technology shows great potential in the rapid synthesis of high-entropy materials. In 2018, Hu et al. used Joule heating technology to synthesize nanoscale high-entropy alloys on carbon nanofibers for the first time, and showed excellent catalytic performance in the synthesis of ammonia (Science 2018, 359, 1489 -1494.). Given that OER involves the breaking and formation of metal oxygen bonds, high-entropy oxide materials are expected to show greater potential in OER applications. For example, Kang et al. prepared high-entropy oxides containing 6 to 10 elements, among which ZnFeNiCuCoRu high-entropy oxides can achieve 10mA cm in 1.0 M KOH solution with an ultra-low overpotential of only 170 mV. -2The current density of 200 MW was 2.37 W·m-1·K-1 (Adv. Mater. 2024, 36, 2308490.). Deng et al. used Joule heating to synthesize high-entropy oxides of various element combinations on a nickel substrate, covering rock salt structure, spinel structure and perovskite structure. The synthesized rock salt structure MgFeCoNiZn oxide has excellent OER performance (Nano Lett. 2022, 22, 6492 -6500.).

[0005] The above studies all show that Joule heating technology shows great potential in the rapid synthesis of high-entropy materials, especially its ability to heat materials to ultra-high temperatures in a very short time. At present, the control of heating time has been widely studied, but the regulation of cooling process is still a relatively underexplored area. It is well known that cooling time has a key influence on the size, morphology, stability and uniformity of crystals. Therefore, how to regulate the cooling time is a key challenge to further improve the catalytic performance of high-entropy materials. Summary of the invention

[0006] In view of the problems in the above prior art that the Joule heating equipment cannot regulate the cooling time and the OER electrocatalyst has poor activity, the present invention provides a method for regulating the cooling time after Joule heating and a high entropy oxide electrocatalyst based thereon, wherein the high entropy oxide electrocatalyst exhibits excellent OER catalytic performance in electrolyzed water.

[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0008] In a first aspect, the present invention provides a method for controlling the cooling time after Joule heating, comprising the following steps:

[0009] (1) Divide the graphite plate by volume to obtain graphite substrates of different masses and surface areas, and calculate the ratio of the mass to the area of ​​each graphite substrate. ;in, is the surface area in cm²; is the mass, in g;

[0010] (2) Under given current and voltage conditions, the graphite substrates with different mass-to-area ratios were heated to 1100 K using a Joule heating device, and the temperature-time curve was recorded to obtain the cooling time of the graphite substrates with different mass-to-area ratios. ;

[0011] (3) Based on Newton’s law of cooling, fitting Cooling time and calculate the specific heat capacity during the convection cooling process. Convective heat transfer coefficient Ratio ;

[0012] (4) Consider the thermal radiation term and add it to the model for correction;

[0013] (5) Determine the cooling time of the graphite substrate and temperature The relational expression of .

[0014] Furthermore, the graphite substrate cooling time With temperature The relational expression is as follows:

[0015]

[0016]

[0017] in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit of is K; is the radiation cooling constant, in units of (sm 2 g -1 ).

[0018] Furthermore, the radiation cooling constant It is obtained by: by taking the mass area ratio as 0.078 g cm -2 The graphite substrate was heated to 1100 K, 1500 K, 1800 K and 2000 K respectively, and it was found that The law of change with temperature is expressed as follows:

[0019]

[0020] in, , and is the fitting parameter in the radiation cooling curve.

[0021] Furthermore, the graphite substrate cooling time With temperature The relational expression is as follows:

[0022]

[0023]

[0024] in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit of is K; , and is the fitting parameter in the radiation cooling curve.

[0025] Furthermore, in step (3), the Cooling time The relationship is as follows:

[0026]

[0027] in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit is K.

[0028] In a second aspect, the present invention provides a high entropy oxide electrocatalyst based on the method.

[0029] In a third aspect, the present invention provides a method for preparing the high entropy oxide electrocatalyst, comprising the following steps:

[0030] S1. preparing a precursor catalyst;

[0031] S2. According to the relationship between cooling time and temperature, select The precursor catalyst is placed on the graphite substrate and heated to room temperature using a Joule heating device. , and after cooling, a high entropy oxide electrocatalyst was obtained.

[0032] Furthermore, the precursor catalyst is prepared by the following method: cutting carbon cloth, soaking it in concentrated sulfuric acid, washing it, and drying it; weighing iron salt, cobalt salt, nickel salt, chromium salt, manganese salt, urea and ammonium fluoride in proportion, adding water to prepare a solution; mixing the prepared solution with the dried carbon cloth, performing a hydrothermal reaction, washing, and drying to obtain a precursor catalyst.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention achieves convenient and precise control of the cooling time of the Joule heating device in the range of 1100 K to 2200 K by adjusting the mass-to-area ratio of the graphite substrate. The control strategy of the present invention can greatly shorten the cooling time and achieve instantaneous cooling. The prepared high-entropy oxide electrocatalyst has a large specific surface area and a stable phase structure, which significantly improves the OER catalytic performance. Among them, the high-entropy oxide electrocatalyst prepared with a cooling time of 0.3 s has a structure of nanowires assembled from fine nanoparticles with a length of about 200 nm, showing the best electrochemical performance at 10 mA cm -2 At a current density of 1.3 Å, the overpotential is only 219 mV.

[0035] (2) The method provided by the present invention is simple and efficient, and can be widely used in the preparation and performance optimization of electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The temperature rise and fall curves of graphite substrates with different mass-to-area ratios;

[0037] Figure 2 is the fitting curve of the mass area ratio of the graphite substrate and the cooling time;

[0038] Figure 3 The mass-to-area ratio is 0.078 g cm -2 The heating and cooling curves of the graphite substrate at a voltage of 20 V and a current of 67.5 A, 100 A, 150 A, and 180 A;

[0039] Figure 4 The mass-to-area ratio is 0.078 g cm -2 The temperature of the graphite substrate and The fitting curve of the value;

[0040] Figure 5 The morphology of the high entropy oxide electrocatalyst prepared at different cooling times; the cooling times corresponding to Figures a, b, c, d, e, and f are 0.3 s, 0.5 s, 1.0 s, 2.0 s, 3.0 s, and 4.0 s, respectively;

[0041] Figure 6 Element distribution of high entropy oxide electrocatalyst by transmission electron microscopy-energy spectrum with a cooling time of 0.3 s;

[0042] Figure 7 The X-ray powder diffraction curves of the high entropy oxide electrocatalysts obtained at different cooling times;

[0043] Figure 8 The OER performance curves of the high entropy oxide electrocatalysts obtained at different cooling times. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention provides a method for controlling the cooling time after Joule heating, comprising the following steps:

[0046] (1) Divide the graphite plate by volume to obtain graphite substrates of different masses and surface areas, and calculate the ratio of the mass to the area of ​​each graphite substrate. ;in, is the surface area in cm²; is the mass, in g;

[0047] (2) Under given current and voltage conditions, the graphite substrates with different mass-to-area ratios were heated to 1100 K using a Joule heating device, and the temperature-time curve was recorded to obtain the cooling time of the graphite substrates with different mass-to-area ratios. ;

[0048] (3) Based on Newton’s law of cooling, fitting Cooling time and calculate the specific heat capacity during the convection cooling process. Convective heat transfer coefficient Ratio ;

[0049] (4) Consider the thermal radiation term and add it to the model for correction;

[0050] (5) Determine the cooling time of the graphite substrate and temperature The relational expression of .

[0051] In the following specific examples, unless otherwise specified, the reagents and raw materials used are all commercially available.

[0052] Example 1

[0053] A method for regulating cooling time, the operating steps are as follows:

[0054] (1) The graphite plate was divided into different volumes, and the mass-area ratios were 0.033 g cm -2 (m = 0.049 g, A = 1.46 cm 2 ), 0.039 g cm -2 (m = 0.175 g, A = 4.45 cm 2 ), 0.078 g cm -2 (m = 0.475 g, A = 6.10 cm 2 ), 0.122 g cm -2 (m = 0.879 g, A = 7.20 cm 2 ), 0.143 g cm -2 (m = 0.895 g, A = 6.25 cm 2 ), 0.163 g cm -2 (m = 1.612 g, A = 9.90 cm 2 ), 0.185 g cm -2 (m = 3.023 g, A = 16.3 cm 2 ), and 0.213 g cm -2 (m = 3.927 g, A = 18.4 cm 2 ) on a graphite substrate.

[0055] (2) Using a Joule heating device, the mass area ratio of the sample was 0.039 g cm at a voltage of 20 V and currents of 30 A, 67.5 A, 130 A, 135 A, 145 A, 170 A, and 250 A. -2 , 0.078 g cm -2 , 0.122 g cm -2 , 0.143 g cm -2 , 0.163 g cm -2 , 0.185 g cm -2 , and 0.213 g cm -2 The graphite substrate is heated to 1100 K. For a mass-to-area ratio of 0.033 g cm -2 The current and voltage were set to 15 A and 10 V, respectively.

[0056] (3) Figure 1 The heating and cooling curves of graphite substrates with different mass-to-area ratios are shown. The mass-to-area ratio is 0.033 gcm -2 , 0.039 g cm -2 , 0.078 g cm -2 , 0.122 g cm -2 , 0.143 g cm -2 , 0.163 g cm -2 , 0.185 g cm -2 , and 0.213 g cm -2 The cooling times of the graphite substrate are 0.3 s, 0.5 s, 1.0 s, 1.6 s, 2.0 s, 2.6s, 3.1 s, and 3.7 s, respectively.

[0057] (4) Based on Newton's law of cooling, the curve of mass-to-area ratio and cooling time is fitted according to the following formula. The obtained curve is as follows: Figure 2 As shown, the calculation is 118.56 s cm 2 g -1 .

[0058]

[0059] in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit is K.

[0060] (5) For graphite substrates above 1100 K, the thermal radiation term is considered and added to the model for correction, and the relationship between the cooling time and temperature is obtained:

[0061]

[0062]

[0063] in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit of is K; is the radiation cooling constant, in units of (sm 2 g -1 ).

[0064] The radiation cooling constant It is obtained by: setting the mass-to-area ratio to 0.078 g cm -2 The graphite substrate was heated to 1100 K, 1500 K, 1800 K, and 2000 K at a voltage of 20 V and a current of 67.5 A, 100 A, 150 A, and 180 A, respectively. The law of temperature change, such as Figure 3 and 4 As shown, further polynomial fitting is used to obtain The relationship between value and temperature:

[0065]

[0066] in, = -7.54 x 10 -5 , = 1.48 x 10 -8 , = 0.064.

[0067] (6) Combined with the above results, the relationship between cooling time and temperature is determined as follows:

[0068]

[0069]

[0070] in, = 118.56 s cm 2 g -1 ; = 298.15 K; = -7.54 x 10 -5 , = 1.48 x 10 -8 , = 0.064.

[0071] Example 2

[0072] Based on the relationship expression between the cooling time and the temperature determined in Example 1, a high entropy oxide electrocatalyst with a cooling time of 0.3 s was prepared, and the operation steps were as follows:

[0073] (1) Immerse the carbon cloth in concentrated sulfuric acid for 24 h, then rinse it with deionized water several times and dry it for later use.

[0074] (2) 1.50 g CoCl 2 6H 2 O, 0.86 g FeCl 3 6H 2 O, 0.51 g NiCl 2 6H 2 O, 0.11 g MnCl 2 ·4H 2 O, 0.14 g CrCl 3 6H 2 O, 2.40 g urea and 0.60 g ammonium fluoride were dissolved in 100 mL water and mixed by magnetic stirring.

[0075] (3) The carbon cloth and the mixed solution in (2) were placed in a 50 mL reactor and heated at 140 °C for 5 h.

[0076] (4) The reactor was cooled to room temperature, the obtained catalyst was taken out, washed with anhydrous ethanol for 5 times, and dried to obtain a precursor catalyst.

[0077] (5) Using the relationship between cooling time and temperature in Example 1, the specific surface area of ​​the graphite substrate corresponding to the cooling time of 0.3 s from 1100 K to room temperature was calculated. The calculated mass-to-area ratio was 0.033 g cm -2 .

[0078] (6) Place the precursor catalyst at a mass area ratio of 0.033 g cm -2 The graphite substrate was then heated to 1100 K using a Joule heating device in an argon atmosphere, and the heating voltage and current were set to 110 V and 89 A, respectively.

[0079] (7) After cooling to room temperature, the catalyst in the Joule heating device was taken out to obtain a high entropy oxide electrocatalyst with a cooling time of 0.3 s.

[0080] The scanning electron microscopy results of the obtained high entropy oxide electrocatalyst are shown in Figure 5 As shown in a. Figure 5As can be seen in a, the structure of the high entropy oxide electrocatalyst is a nanowire assembled from tiny nanoparticles, with a length of about 200 nm; by performing an energy spectrum element surface scanning analysis on the high entropy oxide electrocatalyst, it can be seen that iron, cobalt, nickel, chromium, manganese, and oxygen are evenly distributed (see Figure 6 ). The X-ray powder diffraction analysis of the high entropy oxide electrocatalyst showed that the high entropy oxide electrocatalyst was a single-phase spinel structure at a cooling time of 0.3 s (see Figure 7 ).

[0081] Example 3

[0082] Based on the relationship expression between the cooling time and the temperature determined in Example 1, a high entropy oxide electrocatalyst with a cooling time of 0.5 s was prepared, and the operation steps were as follows:

[0083] (1) Immerse the carbon cloth in concentrated sulfuric acid for 24 h, then rinse it with deionized water several times and dry it for later use.

[0084] (2) 1.50 g CoCl 2 6H 2 O, 0.86 g FeCl 3 6H 2 O, 0.51 g NiCl 2 6 2 O, 0.11 g MnCl 2 ·4H 2 O, 0.14 g CrCl 3 6H 2 O, 2.40 g urea and 0.60 g ammonium fluoride were dissolved in 100 mL water and mixed by magnetic stirring.

[0085] (3) The carbon cloth and the mixed solution in (2) were placed in a 50 mL reactor and heated at 140 °C for 5 h.

[0086] (4) The reactor was cooled to room temperature, the obtained catalyst was taken out, washed with anhydrous ethanol for 5 times, and dried to obtain a precursor catalyst.

[0087] (5) Using the relationship between cooling time and temperature in Example 1, the specific surface area of ​​the graphite substrate corresponding to the cooling time of 0.5 s from 1100 K to room temperature was calculated. The calculated mass-to-area ratio was 0.039 g cm -2 .

[0088] (6) Place the precursor catalyst at a mass area ratio of 0.039 g cm -2The graphite substrate was then heated to 1100 K using a Joule heating device in an argon atmosphere, and the heating voltage and current were set to 110 V and 89 A, respectively.

[0089] (7) After cooling to room temperature, the catalyst in the Joule heating device was taken out to obtain a high entropy oxide electrocatalyst with a cooling time of 0.5 s.

[0090] The scanning electron microscopy results of the obtained high entropy oxide electrocatalyst are shown in Figure 5 As shown in b. Figure 5 As can be seen in b, its morphology is nanoparticles of about 100 nm. X-ray powder diffraction analysis of the high entropy oxide electrocatalyst showed that at a cooling time of 0.5 s, the high entropy oxide electrocatalyst was a single-phase spinel structure (see Figure 7 ).

[0091] Example 4

[0092] Based on the relationship expression between the cooling time and the temperature determined in Example 1, a high entropy oxide electrocatalyst with a cooling time of 1.0 s was prepared, and the operation steps were as follows:

[0093] (1) Immerse the carbon cloth in concentrated sulfuric acid for 24 h, then rinse it with deionized water several times and dry it for later use.

[0094] (2) 1.50 g CoCl 2 6H 2 O, 0.86 g FeCl 3 6H 2 O, 0.51 g NiCl 2 6 2 O, 0.11 g MnCl 2 ·4H 2 O, 0.14 g CrCl 3 6H 2 O, 2.40 g urea and 0.60 g ammonium fluoride were dissolved in 100 mL water and mixed by magnetic stirring.

[0095] (3) The dried carbon cloth and the mixed solution in (2) were mixed in a 50 mL reactor and heated at 140 °C for 5 h.

[0096] (4) The reactor was cooled to room temperature, the obtained catalyst was taken out, washed with anhydrous ethanol for 5 times, and dried to obtain a precursor catalyst.

[0097] (5) Using the relationship between cooling time and temperature in Example 1, the specific surface area of ​​the graphite substrate corresponding to the cooling time of 1.0 s from 1100 K to room temperature was calculated. The calculated mass-to-area ratio was 0.078 g cm -2 .

[0098] (6) Place the precursor catalyst at a mass area ratio of 0.078 g cm -2 The graphite substrate was then heated to 1100 K using a Joule heating device in an argon atmosphere, and the heating voltage and current were set to 110 V and 89 A, respectively.

[0099] (7) After cooling to room temperature, the catalyst in the Joule heating device is taken out to obtain a high entropy oxide electrocatalyst with a cooling time of 1.0 s.

[0100] The scanning electron microscopy results of the obtained high entropy oxide electrocatalyst are shown in Figure 5 c. Figure 5 c shows that the morphology is nanoparticles of different sizes. X-ray powder diffraction analysis of the high entropy oxide electrocatalyst shows that at a cooling time of 1.0 s, the high entropy oxide electrocatalyst is a mixture of rock salt and spinel structures (see Figure 7 ).

[0101] Example 5

[0102] Based on the relationship expression between the cooling time and the temperature determined in Example 1, a high entropy oxide electrocatalyst with a cooling time of 2.0 s was prepared, and the operation steps were as follows:

[0103] (1) Immerse the carbon cloth in concentrated sulfuric acid for 24 h, then rinse it with deionized water several times and dry it for later use.

[0104] (2) 1.50 g CoCl 2 6H 2 O, 0.86 g FeCl 3 6H 2 O, 0.51 g NiCl 2 6 2 O, 0.11 g MnCl 2 ·4H 2 O, 0.14 g CrCl 3 6H 2 O, 2.40 g urea and 0.60 g ammonium fluoride were dissolved in 100 mL water and mixed by magnetic stirring.

[0105] (3) The dried carbon cloth and the mixed solution in (2) were mixed in a 50 mL reactor and heated at 140 °C for 5 h.

[0106] (4) The reactor was cooled to room temperature, the obtained catalyst was taken out, washed with anhydrous ethanol for 5 times, and dried to obtain a precursor catalyst.

[0107] (5) Using the relationship between cooling time and temperature in Example 1, the specific surface area of ​​the graphite substrate corresponding to the cooling time of 2.0 s from 1100 K to room temperature was calculated. The calculated mass-to-area ratio was 0.143 g cm -2 .

[0108] (6) Place the precursor catalyst at a mass area ratio of 0.143 g cm -2 The graphite substrate was then heated to 1100 K using a Joule heating device in an argon atmosphere, and the heating voltage and current were set to 110 V and 89 A, respectively.

[0109] (7) After cooling to room temperature, the catalyst in the Joule heating device was taken out to obtain a high entropy oxide electrocatalyst with a cooling time of 2.0 s.

[0110] The scanning electron microscopy results of the obtained high entropy oxide electrocatalyst are shown in Figure 5 d. Figure 5 As can be seen in Figure d, its morphology is nanoparticles of different sizes. The X-ray powder diffraction analysis of the high entropy oxide electrocatalyst showed that at a cooling time of 2.0 s, the high entropy oxide electrocatalyst was a mixture of rock salt and spinel structures (see Figure 7 ).

[0111] Example 6

[0112] Based on the relationship expression between the cooling time and the temperature determined in Example 1, a high entropy oxide electrocatalyst with a cooling time of 3.0 s was prepared, and the operation steps were as follows:

[0113] (1) Immerse the carbon cloth in concentrated sulfuric acid for 24 h, then rinse it with deionized water several times and dry it for later use.

[0114] (2) 1.50 g CoCl 2 6H 2 O, 0.86 g FeCl 3 6H 2 O, 0.51 g NiCl 2 6 2 O, 0.11 g MnCl 2 ·4H 2O, 0.14 g CrCl 3 6H 2 O, 2.40 g urea and 0.60 g ammonium fluoride were dissolved in 100 mL water and mixed by magnetic stirring.

[0115] (3) The dried carbon cloth and the mixed solution in (2) were mixed in a 50 mL reactor and heated at 140 °C for 5 h.

[0116] (4) The reactor was cooled to room temperature, the obtained catalyst was taken out, washed with anhydrous ethanol for 5 times, and dried to obtain a precursor catalyst.

[0117] (5) Using the relationship between cooling time and temperature in Example 1, the specific surface area of ​​the graphite substrate corresponding to the cooling time of 3.0 s from 1100 K to room temperature was calculated. The calculated mass-to-area ratio was 0.185 g cm -2 .

[0118] (6) Place the precursor catalyst at a mass area ratio of 0.185 g cm -2 The graphite substrate was then heated to 1100 K using a Joule heating device in an argon atmosphere, and the heating voltage and current were set to 110 V and 89 A, respectively.

[0119] (7) After cooling to room temperature, the catalyst in the Joule heating device was taken out to obtain a high entropy oxide electrocatalyst with a cooling time of 3.0 s.

[0120] The scanning electron microscopy results of the obtained high entropy oxide electrocatalyst are shown in Figure 5 As shown in e. Figure 5 As can be seen in Figure e, its morphology is nanoparticles of 200 nm to 300 nm. X-ray powder diffraction analysis of the high entropy oxide electrocatalyst showed that at a cooling time of 3.0 s, the high entropy oxide electrocatalyst was a mixture of rock salt and spinel structures (see Figure 7 ).

[0121] Example 7

[0122] Based on the relationship expression between the cooling time and the temperature determined in Example 1, a high entropy oxide electrocatalyst with a cooling time of 4.0 s was prepared, and the operation steps were as follows:

[0123] (1) Immerse the carbon cloth in concentrated sulfuric acid for 24 h, then rinse it with deionized water several times and dry it for later use.

[0124] (2) 1.50 g CoCl 2 6H 2 O, 0.86 g FeCl3 6H 2 O, 0.51 g NiCl 2 6 2 O, 0.11 g MnCl 2 ·4H 2 O, 0.14 g CrCl 3 6H 2 O, 2.40 g urea and 0.60 g ammonium fluoride were dissolved in 100 mL water and mixed by magnetic stirring.

[0125] (3) The dried carbon cloth and the mixed solution in (2) were mixed in a 50 mL reactor and heated at 140 °C for 5 h.

[0126] (4) The reactor was cooled to room temperature, the obtained catalyst was taken out, washed with anhydrous ethanol for 5 times, and dried to obtain a precursor catalyst.

[0127] (5) Using the relationship between cooling time and temperature in Example 1, the specific surface area of ​​the graphite substrate corresponding to the cooling time of 4.0 s from 1100 K to room temperature was calculated. The calculated mass-to-area ratio was 0.213 g cm -2 .

[0128] (6) Place the precursor catalyst at a mass area ratio of 0.213 g cm -2 The graphite substrate was then heated to 1100 K using a Joule heating device in an argon atmosphere, and the heating voltage and current were set to 110 V and 89 A, respectively.

[0129] (7) After cooling to room temperature, the catalyst in the Joule heating device was taken out to obtain a high entropy oxide electrocatalyst with a cooling time of 4.0 s.

[0130] The scanning electron microscopy results of the obtained high entropy oxide electrocatalyst are shown in Figure 5 f. Figure 5 f, its morphology is aggregated nanoparticles. X-ray powder diffraction analysis of the high entropy oxide electrocatalyst showed that at a cooling time of 4.0 s, the high entropy oxide electrocatalyst was a mixture of rock salt and spinel structures (see Figure 7 ).

[0131] The high entropy oxide electrocatalysts prepared in Examples 2 to 7 were applied to electrolyze water:

[0132] A three-electrode system was used, with the high entropy oxide electrocatalyst prepared at different cooling times as the working electrode, mercuric oxide and graphite rod as the reference electrode and counter electrode respectively, and the electrolyte was 1.0 M KOH; the test environment was room temperature. The relationship between the mercuric oxide standard electrode and the reversible hydrogen potential is:

[0133] E RHE = E Hg / HgO + 0.0591 x pH + 0.098

[0134] (1) Test preparation: The high entropy oxide electrocatalysts prepared in Examples 2 to 7 were immersed in 1.0 M KOH with an exposure area of ​​0.20 cm 2 , connect them to the electrochemical workstation as working electrodes, and connect the circuits of the counter electrode and the reference electrode.

[0135] (2) Test process: at 1.0 V RHE to 1.25 V RHR The working electrode was activated by cyclic voltammetry for 20 cycles at a potential range of 1.1 V. RHE to 1.7 V RHE The polarization curve is tested within the range, and the results are as follows Figure 8 As shown, from Figure 8 It can be seen that under alkaline conditions, the high entropy oxide electrocatalyst with a cooling time of 0.3 s at a current density of 10 mAcm -2 Table 1 shows the specific values ​​of the electrochemical performance of the high entropy oxide electrocatalysts prepared in Examples 2 to 7 under 1.0 M KOH conditions.

[0136] Table 1: Specific values ​​of electrochemical properties of high entropy oxide electrocatalysts prepared in Examples 2 to 7

[0137]

[0138] As can be seen from Table 1, with the shortening of the cooling time (the natural cooling time of a standard-sized graphite substrate in a Joule heating device is 3–5 s), the prepared high-entropy oxide electrocatalyst has a higher current density of 10 mA cm -2 The required overpotential shows a decreasing trend. The high entropy oxide electrocatalyst with a cooling time of 0.3 s at a current density of 10 mA cm -2 The required overpotential is only 219 mV.

[0139] In summary, the present invention achieves convenient and precise control of the cooling time of the Joule heating equipment in the range of 1100 K to 2000 K by adjusting the mass-to-area ratio of the graphite substrate; the control strategy of the present invention can greatly shorten the cooling time and achieve instantaneous cooling. The prepared high-entropy oxide electrocatalyst has a large specific surface area and a stable phase structure, which significantly improves the OER catalytic performance.

[0140] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A method for controlling the cooling time after Joule heating, characterized in that: The following steps are involved: a. Divide the graphite plate by volume to obtain graphite substrates of different masses and surface areas, and calculate the ratio of mass to area of ​​each graphite substrate ;in, is the surface area in cm²; is the mass, in g; b. Under given current and voltage conditions, use a Joule heating device to heat graphite substrates with different mass-to-area ratios to 1100 K, and record the temperature-time curve to obtain the cooling time of graphite substrates with different mass-to-area ratios. ; c. Based on Newton's law of cooling, fitting Cooling time and calculate the specific heat capacity during the convection cooling process. Convective heat transfer coefficient Ratio ; d. Consider the thermal radiation term and add it to the model for correction; e. Determine the cooling time of graphite substrate and temperature The relational expression of .

2. The method for controlling the cooling time after Joule heating according to claim 1, characterized in that: The graphite substrate cooling time With temperature The relational expression is as follows: ; ; in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit of is K; is the radiation cooling constant, in units of (sm 2 g -1 ).

3. The method for controlling the cooling time after Joule heating according to claim 2, characterized in that: The radiation cooling constant It is obtained by: by taking the mass area ratio as 0.078 g cm -2 The graphite substrate was heated to 1100 K, 1500 K, 1800 K and 2000 K respectively, and it was found that The law of change with temperature is expressed as follows: ; in, , and is the fitting parameter in the radiation cooling curve.

4. The method for controlling the cooling time after Joule heating according to claim 2, characterized in that: The graphite substrate cooling time With temperature The relational expression is as follows: ; ; in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit of is K; , and is the fitting parameter in the radiation cooling curve.

5. The method for controlling the cooling time after Joule heating according to claim 1, characterized in that: In step c, Cooling time The relationship is as follows: ; in, is the surface area, For quality, is the specific heat capacity, is the convective heat transfer coefficient, , and Respectively The temperature at the moment, the initial temperature of the material and the ambient temperature, , and The unit is K.

6. A high entropy oxide electrocatalyst based on the method according to any one of claims 1 to 5.

7. The method for preparing a high entropy oxide electrocatalyst according to claim 6, characterized in that: The following steps are involved: S1. preparing a precursor catalyst; S2. According to the relationship between cooling time and temperature, select The precursor catalyst is placed on the graphite substrate and heated to room temperature using a Joule heating device. , and after cooling, a high entropy oxide electrocatalyst was obtained.

8. The method for preparing a high entropy oxide electrocatalyst according to claim 7, characterized in that: The precursor catalyst is prepared by the following method: cutting carbon cloth, soaking it in concentrated sulfuric acid, washing it, and drying it; weighing iron salt, cobalt salt, nickel salt, chromium salt, manganese salt, urea and ammonium fluoride in proportion, adding water to prepare a solution; mixing the prepared solution with the dried carbon cloth, performing a hydrothermal reaction, washing it, and drying it to obtain a precursor catalyst.

Citation Information

Patent Citations

  • Graphene-coated high-entropy oxide nanoparticle catalyst as well as preparation method and application thereof

    CN116145152A

  • Preparation method of three-dimensional high-specific-surface-area high-entropy metal oxide oxygen evolution catalyst

    CN116949487A

Cited By

  • Ruthenium-based ammonia synthesis catalyst based on high-entropy oxide carrier as well as preparation and application of ruthenium-based ammonia synthesis catalyst

    CN121669226A

  • Ruthenium-based ammonia synthesis catalysts based on high-entropy oxide supports and preparation and use thereof

    CN121669226B